Pengaruh Mengajar Yang Bervariasi Terhadap Prestasi Belajar Siswa di SMP ELPIDA Kelas VII - Yanto Tefa; Yublina Tefa; Prihadi Kristiyan; Elisabeth Dethan (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2021)
This study is based on the fact that the need for competent teachers in the learning process is very necessary, because the main problem in this study is how much influence varies teaching on student learning achievement in ELPIDA Junior High School (Class VII) and how effective the implementation of varied teaching is on student learning achievement in ELPIDA Junior High School (Class VII). The method used in this study is Quantitative research with a classroom research strategy. Based on the results of the research conducted, it shows that with this student achievement, teachers can find out "whether the application of varied teaching affects student learning achievement" at ELPIDA Junior High School. From the results of the simple regression analysis, it can be concluded that the influence of varying teaching on student learning achievement is very high, namely the diterminant coefficient / KP 29.1% and the value of variable relationships is greater than the standard table, which is 0.980 > 0.428 based on these calculations, then the H1 hypothesis is accepted. Thus, the hypothesis that teaching varies has a significant effect on learning performance in Elpida Junior High School grade VII, has been proven.